On the Importance of Future, Precise, X-ray Measurements in Kaonic Atoms - Sławomir Wycech; Kristian Piscicchia (Condensed Matter, 2024)
Progress in the construction of precise X-ray detectors allows measurements of energies and widths of “upper levels” in K− mesic atoms. These can be used to determine sub-threshold Kaon-nucleon amplitudes, which are important in investigations of nuclear states of these mesons. The special case of the 2P state in Kaonic Helium is discussed and used to check the properties of the K− proton quasi-bound state. Similar attempts in other elements indicate a need for new, precise measurements.